2007
DOI: 10.5902/198050981940
|View full text |Cite
|
Sign up to set email alerts
|

Clima e vegetação natural do estado do Rio Grande do Sul segundo o diagrama climático de Walter e Lieth.

Abstract: RESUMORelacionou-se a vegetação natural do estado do Rio Grande do Sul com as disponibilidades climáticas por meio do diagrama climático de Walter e Lieth (1967). Foram utilizadas as temperaturas médias mensais do ar e as médias dos totais mensais de chuva de 41 estações meteorológicas, no período de . Para cada estação meteorológica foi traçado um gráfico cartesiano no qual se colocaram, no eixo das abcisssas, os meses e, num dos eixos das ordenadas, a temperatura média mensal do ar, em °C e, no outro, a médi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 2 publications
(2 reference statements)
0
15
0
8
Order By: Relevance
“…In most months, the temperature remained within the historical range of mean temperatures recorded for the region of the Sinos River Basin (Moreno, 1961;Buriol et al, 2007). However, in November 2012, the high temperature recorded in the urban environment of Taquara (mean of 34.3 °C) may have contributed to the increased MCN frequency.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In most months, the temperature remained within the historical range of mean temperatures recorded for the region of the Sinos River Basin (Moreno, 1961;Buriol et al, 2007). However, in November 2012, the high temperature recorded in the urban environment of Taquara (mean of 34.3 °C) may have contributed to the increased MCN frequency.…”
Section: Discussionmentioning
confidence: 94%
“…Pereira et al (2013) showed that 88.01% of the MCN frequency was predicted by the combination of the number of vehicles and the relative humidity in the municipality of Uberlândia (Minas Gerais, Brazil), with the first variable contributing 83.92%. It is noteworthy that the climate in Rio Grande do Sul is humid all year long (Buriol et al, 2007), differently from the southeast region of Brazil where the other studies were conducted. This may be related to the fact that there was no relation between the MCN frequency and humidity.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Na classificação de Walter, sobre os zonobiomas terrestres, o estado do Rio Grande do Sul é enquadrado no Zonobioma V: clima temperado úmido, correspondente à vegetação natural de florestas sempre verdes (BURIOL, 2007). Entretanto, apesar de o estado apresentar um clima típico de florestas, cerca de 46,3% de sua vegetação natural é formada por áreas de campo (MARCHIORI, 2002(MARCHIORI, , 2004.…”
Section: -Paisagem Naturalunclassified
“…The soil is classified as organic; it is poorly drained and contains organic material in different stages of decomposition (Streck et al 2002). The climate of Rio Grande do Sul is humid throughout the year (Buriol et al 2007). According to the Köppen classification system, the climate of the region under study is type Cfa (humid subtropical), with average temperatures that exceed 22°C in the warmest month.…”
Section: Study Areamentioning
confidence: 99%